Entre escolas, clubs e sociedades: as Gymnasticas tecidas por professores no Rio de Janeiro (1850-1900) - Anna Luiza Ferreira Romao (2016)
This study aims to contribute to the field of research that investigates the History of Gymnastica (Gymnastics) in Brazil. Considering different contexts in Rio de Janeiro, and having two Gymnastica teachers as a guiding principle, my objective is to comprehend the process through which Gymnastica was shaped in that Brazilian city during the second half of the nineteenth century. Thus, I emphasize the participation of Paulo Vidal and Vicente Casali, who, circulating in diverse and distinct academic and non-academic institutions, building their sociability networks, systematizing and disseminating their practices and knowledge, helped the process of constitution and affirmation of Gymnastica in Brazil, and, at the same time, were shaped as teachers of this physical education and training. The documentary corpus analyzed here consists of: newspapers and magazines that circulated in Rio de Janeiro between 1850 e 1900; a Rui Barbosa´s statement (1882); minutes and statements from Congresso da Instrucção do Rio de Janeiro (1884); speeches delivered by directors of some institutions, in which they presented a brief history of these teaching and formation places; paystubs; a list containing names of these places administrators and teachers; a Gymnastica teaching program; letters written by gymnastica teachers to the institutions directors or rectors; requests for the purchase of or repair to equipment used in Gymnastica classes; statutes, regulations and internal rules that organized and coordinated these places; contracts and Gymnastica teachers/masters dismissal requests; timesheets from different institutions. First, I present a panorama of Rio de Janeiro, identifying the institutions where Paulo Vidale Vicente Casali circulated; trying to find out elements that constituted their sociability networks; and paying attention to the encounters and exchanges they experienced in several spheres of Rio de Janeiros society. Next, I discuss the presence of foreigners in that city and their contributions to change its structure and modernize it. To do so, I takefor reference three non-academic institutions one from France (Sociedade Franceza de Gymnastica) and two from Portugal (Club Gymnastico Portuguez and Congresso Gymnastico Portuguez) where both Paulo Vidal and Vicente Casali worked. Taking into account the ideas and movements which took place at that time, I seek to understand these institutions organization and operating forms, emphasizing the presence of Gymnastica and the elements that characterized it as a practice shaped in these spaces of sociability. Then, paying attention to the rules and regulations, the forms of organization and operation, I try to comprehend how Gymnastica entered the academic institutions, and how these places shaped it. At this point, I also analyze Collegio Pedro II and Escola Normal da Côrte more carefully. Finally, I emphasize both the instances and the people that defended the practice of Gymnastica during the second half of the nineteenth century.